Model of care for individuals with rare cancer predisposition syndromes in Germany - Valentina Härter; Birte Sänger; Josephine C. Gieseke; Tanja Gerasimov; Beatrice Hoffmann; Carolin Huisinga; Anja Karow; Lucas J. Müntnich; Natalie E. Palmaers; Stefanie Paquet; Judith Penkert; Diane M. Renz; et al. (The Lancet Regional Health. Europe)
Summary: Genetic cancer predisposition is an important cause of cancer across all age groups. Approximately ten percent of cancer patients have an underlying cancer predisposition syndrome (CPS) and we estimate that 500,000 individuals with a CPS live in Germany. Gene panel germline or tumour-germline genetic testing is increasingly employed in cancer patients resulting in rising numbers of CPS diagnoses. Such a diagnosis is only useful if affected individuals are appropriately counselled and if recommended clinical consequences in the areas of cancer prevention, surveillance, and therapy can be implemented. While care pathways for individuals with hereditary breast and ovarian cancer and familial colon cancer syndromes exist, sufficient interdisciplinary care structures for individuals with rare CPSs are currently lacking. The aim of this viewpoint is to point out that the clinical care pathways for individuals with rare CPSs need to be improved. We describe a model CPS clinic that systematically collects data to allow future evidence-based adaptation of care and propose the establishment of a collaborating network of similar clinics in Germany. This message is directed to individuals with a CPS, health care providers, insurance companies, and politicians in Germany and may be relevant for other health care systems as well.